ANALISIS TRANSFORMASI STRUKTUR PEREKONOMIAN SEKTOR PRIMER, SEKTOR SEKUNDER, DAN SEKTOR TERSIER KABUPATEN BONE BOLANGO - Harijono Imbran (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2022)
This study aims to find out analyzing the transformation of the economic structure of Bone Bolango Regency and how the shift-share distribution through LQ analysis and shift-share Bone Bolango Regency in encouraging economic growth. This study uses a quantitative approach. Data analysis uses secondary data sources for the last 5 years (time-series) and the analytical tools used are Location Question (LQ) and Shift Share Analysis (SSA) analysis.The results of the study indicate that the transformation of the economic structure of Bone Bolango Regency is still not going well, or is still categorized as slow. This can be seen from the contribution of the primary sector share which is still very dominant where the average is 42.60 percent every year. Far above the secondary sector and tertiary sector. The economic potential of Bone Bolango Regency can be seen from the basic sector owned which consists of 10 sectors or business fields, respectively: 1) Mining and Quarrying, 2) Manufacturing Industry, 3) Construction, 4) Wholesale and Retail Trade, 5) Real Estate Estate, 6) Corporate Services, 7) Government Administration, 8) Education Services, 9) Health Services, and 10) Other Services. The non-base sector of Bone Bolango Regency consists of 7 sectors or respective business fields; 1) Agriculture, 2) Procurement of Electricity and Gas, 3) Transportation and Warehousing, 4) Procurement of Water, Garbage, and Waste, 5) Provision of Accommodation and Food and Drink, 6) Information and Communication, and 7) Financial and Insurance Services.